An Extension of Stolarsky Means to the Multivariable Case - Slavko Simic (International Journal of Mathematics and Mathematical Sciences, 2009)
We give an extension of well-known Stolarsky means to the multivariable case in a simple and applicable way. Some basic inequalities concerning this matter are also established with applications in Analysis and Probability Theory.